A Survey of Task Scheduling Methods in Cloud Computing - Nallakumar, R; Sengottaiyan, N; Nithya, S (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is one of the latest computing technology where the data’s applications and the IT services are provided with the help of Internet. The Grid computing, distributed computing and virtualization are the concepts that helped to build the cloud computing. Cloud computing provides various computing resources to the cloud users based on pay-per-usage basis. Resource scheduling and Job/Task scheduling are the most important considerations in the cloud and in which, the jobs submitted gets allocated by the resources efficiently. The goal of the cloud computing service provider, is to use the efficient resources to obtain the maximum profit and this results the task scheduling a core and one of the challenging issues in the cloud environment. The Task scheduling is an NP-hard optimization problem and where the meta-heuristic algorithms are proposed to provide an optimal solution. The scheduling strategy of a good task scheduler should get adopted based on the changing environments and the type of task scheduling used.